Econometric Modelling of Short Run Parsimonious and Long Run Co-integrated Real Exchange Rate Determinants in Kenya - Otieno , Bunde Aggrey (African Journal of Education,Science and Technology (AJEST), 2017)
country’s exchange rate is an important determinant of the growth of its cross border trading and it serves as a measure of international competitiveness. Appreciation of the shilling real exchange rate in Kenya attracted public attention in the last decades, especially from exporters and importers who have argued that the weakening shilling is eroding their competitiveness. The objective of this study was to investigate parameters influencing real exchange rate in Kenya. The data comprised of annual time series data for Kenya over the sample period 1960 to 2010.The study was guided by Montiel’s theory.In this theoretical model, economy’s endogenous variables are determined by predetermined and exogenous policy variables.Predetermined variables are endogenous variables that change slowly over time and exogenous policy variables include fiscal and monetary policy variables, trade policies and variables under the control of domestic authorities. The study adopted Error Correction Model, because of its ability to induce flexibility by combining the short run dynamic and long run equilibrium model in a unified system. Inferential statistics were applied using PC Give, unit root, co integration and granger causality tests were done prior to estimation. The use of cointegration technique allowed the study to capture the equilibrium relationship between non-stationary series within a stationary model. The results of long run co-integrated equilibrium and short-run parsimonious real exchange rate models revealed that real exchange rate is influenced by internal factors such as aid, government expenditure, technological progress, nominal exchange rate and commercial policy stance. External factors proxied by terms of trade also tend to play a critical role as they lead to real exchange rate depreciation. The study concluded that policy management need to focus on ensuring the prevalence of sound macroeconomic fundamentals and effectively target and manage all variables influencing long run behavior of real exchange rate in Kenya.